THE STRUCTURE OF TEACHING AND ITS PEDAGOGICAL-PSYCHOLOGICAL ASPECTS BASED ON A HIERARCHICAL APPROACH IN MODERN EDUCATION (European Journal of Pedagogical Initiatives and Educational Practices, 2025)
This article presents the idea that in the era of the development of the modern education system, one of the various approaches to the effective organization and management of education is the hierarchical education system, and hierarchy is a system based on orderly, leveled, and step-by-step development. In education, this approach is based on the fact that it envisages the complete formation of the student through the gradual acquisition of knowledge and competencies.